Treatment of metastatic pancreatic cancer – present and future perspectives - Świeboda-Sadlej, Anna; Piyush, Vyas; Heleniak, Hubert; Staszewska-Skurczyńska, Marzanna; Kocik, Janusz (Contemporary Oncology/Współczesna Onkologia, 2007)
Pancreatic cancer is one of the most common causes of deaths related to cancer. Results of pancreatic cancer treatment are poor. At present, the standard treatment of metastatic pancreatic cancer hinges on gemcitabine monotherapy, which allows better symptomatic control and slight prolongation of survival time as compared to the treatment with 5-FU only. Erlotinib, a recently registered epidermal growth factor receptor (EGFR) inhibitor, administered in combination with gemcitabine leads to further prolongation of survival time. Because results of treatment of metastatic pancreatic cancer are far from being satisfactory, they are a subject of various clinical trials. In this article the most important of them are reviewed. Various combinations of gemcitabine with other cytostatic drugs have been evaluated, but the majority of them did not show increased activity when compared to the present standard treatment. The most promising combinations are GEM/capecitabine and GEM/platin analogues, especially for patients with a very good performance status. With the advancement of knowledge concerning biology of pancreatic cancer, significant interest was generated in targeted therapies for the treatment of this neoplasia. The key role in the carcinogenesis of pancreatic cancer seems to be played by overexpression of EGFR and activation of signal pathways related to EGFR. Therefore, drugs inhibiting EGFR are of special interest. In contrast to the drug mentioned earlier, i.e. erlotinib, cetuximab, a monoclonal antibody against EGFR, has not shown prolongation of survival of patients with pancreatic cancer. Moreover, addition of bevacizumab to gemcitabine did not increase its activity; nor did it prolong survival. Currently trials are being conducted investigating the escalation of erlotinib dosage as well as combination therapies of erlotinib with other synergistically acting drugs. Currently, a phase III trial evaluating the effect of simultaneous administration of gemcitabine, cetuximab and bevacizumab is running. Also under evaluation are trials regarding non-gemcitabine regimens as a first line treatment. Controversial is second line treatment in advanced pancreatic cancer especially after gemcitabine treatment failure. Initial results have shown that among 2 nd line treatments, some efficacy has been demonstrated by oxaliplatin as well as by combination therapy of docetaxel-capecitabine. Despite some progress made within the last few years, pancreatic cancer is still a very difficult cancer to treat and it is necessary to search for new ways of fighting this disease.